Aqueous Two‐Phase Emulsion Bioink‐Enabled 3D Bioprinting of Porous Hydrogels - Ying, Guo‐Liang; Jiang, Nan; Maharjan, Sushila; Yin, Yi‐Xia; Chai, Rong‐Rong; Cao, Xia; Yang, Jing‐Zhou; Miri, Amir K.; Hassan, Shabir; Zhang, Yu Shrike (Advanced materials (Weinheim), 2018)
3D bioprinting technology provides programmable and customizable platforms to engineer cell‐laden constructs mimicking human tissues for a wide range of biomedical applications. However, the encapsulated cells are often restricted in spreading and proliferation by dense biomaterial networks from gelation of bioinks. Herein, a cell‐benign approach is reported to directly bioprint porous‐structured hydrogel constructs by using an aqueous two‐phase emulsion bioink. The bioink, which contains two immiscible aqueous phases of cell/gelatin methacryloyl (GelMA) mixture and poly(ethylene oxide) (PEO), is photocrosslinked to fabricate predesigned cell‐laden hydrogel constructs by extrusion bioprinting or digital micromirror device‐based stereolithographic bioprinting. The porous structure of the 3D‐bioprinted hydrogel construct is formed by subsequently removing the PEO phase from the photocrosslinked GelMA hydrogel. Three different cell types (human hepatocellular carcinoma cells, human umbilical vein endothelial cells, and NIH/3T3 mouse embryonic fibroblasts) within the 3D‐bioprinted porous hydrogel patterns show enhanced cell viability, spreading, and proliferation compared to the standard (i.e., nonporous) hydrogel constructs. The 3D bioprinting strategy is believed to provide a robust and versatile platform to engineer porous‐structured tissue constructs and their models for a variety of applications in tissue engineering, regenerative medicine, drug development, and personalized therapeutics. An aqueous two‐phase emulsion bioink is developed to create bioprinted porous‐structured hydrogel constructs. Interconnected micropores within the bioprinted hydrogel constructs enhance the growth, spreading, and proliferation of encapsulated living cells.